2020
DOI: 10.21203/rs.2.21482/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global dissection of the BAHD acyltransferase gene family in soybean: Expression profiling, metabolic functions, and evolution

Abstract: Background: Members of the BAHD acyltransferase (ACT) family play important roles in plant defence against biotic and abiotic stresses. Previous genome-wide studies explored different acyltransferase gene families, but not a single study was found so far on the overall genome-wide or positive selection analyses of the BAHD family genes in Glycine max . A better understanding of the functions that specific members of this family play in stress defence can lead to better breeding strategies for stress tolerance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 86 publications
3
3
0
Order By: Relevance
“…However, the number of genes within a gene family can vary among species (Rezaee et al, 2020;Song et al, 2020;Abdullah et al, 2021a;Faraji et al, 2021). The identified tcBAHDs showed high diversity based on sequence structure, physicochemical properties, functions, and distribution across the chromosome, which is in agreement with previous reports of the BAHD gene family (Moglia et al, 2016;Zhang et al, 2019;Ahmad et al, 2020b;Liu et al, 2020a). The annotation retrieved from the Ensembl indicates the identified tcBAHD enzymes have high diversity in the function of tcBAHD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the number of genes within a gene family can vary among species (Rezaee et al, 2020;Song et al, 2020;Abdullah et al, 2021a;Faraji et al, 2021). The identified tcBAHDs showed high diversity based on sequence structure, physicochemical properties, functions, and distribution across the chromosome, which is in agreement with previous reports of the BAHD gene family (Moglia et al, 2016;Zhang et al, 2019;Ahmad et al, 2020b;Liu et al, 2020a). The annotation retrieved from the Ensembl indicates the identified tcBAHD enzymes have high diversity in the function of tcBAHD.…”
Section: Discussionsupporting
confidence: 88%
“…Wholegenome analyses provide information about the genetic basis of response to abiotic and biotic stresses (Motamayor et al, 2013). In particular, genome-wide studies of the BAHD family have been reported in various species, including Populus (Yu et al, 2009), Arabidopsis (Yu et al, 2009), soybean (Ahmad et al, 2020b), Cynara cardunculus (Moglia et al, 2016), and in some species of Rosaceae (Zhang et al, 2019;Liu et al, 2020a). The chromosome-level genome assembly of T. cacao (Motamayor et al, 2013;Argout et al, 2017) provides resources for the characterization of gene families, which has led to the identification and characterization of WRKY (Dayanne et al, 2017), NAC (Shen et al, 2020), GASA (Abdullah et al, 2021a), and MGT (Heidari et al, 2021a) in cacao.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of genes within a gene family can vary among species (Rezaee et al, 2020;Song et al, 2020;Abdullah et al, 2021a;Faraji et al, 2021). The identified tcBAHDs showed high diversity based on sequence structure, physicochemical properties, functions, and distribution across the chromosome, which is in agreement with previous reports of the BAHD gene family (Moglia et al, 2016;Zhang et al, 2019;Ahmad et al, 2020b;Liu et al, 2020a). The annotation retrieved from the Ensembl indicates the identified tcBAHD enzymes have high diversity in the function of tcBAHD.…”
Section: Discussionsupporting
confidence: 88%
“…Wholegenome analyses provide information about the genetic basis of response to abiotic and biotic stresses (Motamayor et al, 2013). In particular, genome-wide studies of the BAHD family have been reported in various species, including Populus (Yu et al, 2009), Arabidopsis (Yu et al, 2009), soybean (Ahmad et al, 2020b), Cynara cardunculus (Moglia et al, 2016), and in some species of Rosaceae (Zhang et al, 2019;Liu et al, 2020a). The chromosome-level genome assembly of T. cacao (Motamayor et al, 2013;Argout et al, 2017) provides resources for the characterization of gene families, which has led to the identification and characterization of WRKY (Dayanne et al, 2017), NAC (Shen et al, 2020), GASA (Abdullah et al, 2021a), and MGT (Heidari et al, 2021a) in cacao.…”
Section: Introductionmentioning
confidence: 99%
“…Wholegenome analyses provide information about the genetic basis of response to abiotic and biotic stresses (Motamayor et al, 2013). In particular, genome-wide studies of the BAHD family have been reported in various species, including Populus (Yu et al, 2009), Arabidopsis (Yu et al, 2009), soybean (Ahmad et al, 2020b), Cynara cardunculus (Moglia et al, 2016), and in some species of Rosaceae (Zhang et al, 2019;Liu et al, 2020a). The chromosome-level genome assembly of T. cacao (Motamayor et al, 2013;Argout et al, 2017) provides resources for the characterization of gene families, which has led to the identification and characterization of WRKY (Dayanne et al, 2017), NAC (Shen et al, 2020), GASA (Abdullah et al, 2021a), and MGT (Heidari et al, 2021a) in cacao.…”
Section: Introductionmentioning
confidence: 99%